2017
DOI: 10.3389/fpls.2016.02024
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Circular RNAs and Their Targets in Leaves of Triticum aestivum L. under Dehydration Stress

Abstract: Circular RNAs (circRNAs) are a type of newly identified non-coding RNAs through high-throughput deep sequencing, which play important roles in miRNA function and transcriptional controlling in human, animals, and plants. To date, there is no report in wheat seedlings regarding the circRNAs identification and roles in the dehydration stress response. In present study, the total RNA was extracted from leaves of wheat seedlings under dehydration-stressed and well-watered conditions, respectively. Then, the circRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
125
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(131 citation statements)
references
References 40 publications
5
125
0
1
Order By: Relevance
“…At present, an increasing number of studies have shown that circular RNA (circRNA) is involved in the regulation of plant responses to various biotic and abiotic stresses. Wang et al () identified 88 circRNAs in wheat, of which 62 were differentially expressed under water stress, indicating that these circRNAs may play a role in response to water stress. In tomato, Zuo et al () identified 854 circRNAs, of which 163 circRNAs were differentially expressed in tomato fruits under control and chilling treatments, and 102 circRNAs could be combined as molecular sponges with 24 miRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…At present, an increasing number of studies have shown that circular RNA (circRNA) is involved in the regulation of plant responses to various biotic and abiotic stresses. Wang et al () identified 88 circRNAs in wheat, of which 62 were differentially expressed under water stress, indicating that these circRNAs may play a role in response to water stress. In tomato, Zuo et al () identified 854 circRNAs, of which 163 circRNAs were differentially expressed in tomato fruits under control and chilling treatments, and 102 circRNAs could be combined as molecular sponges with 24 miRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…As with other ncRNAs, circRNAs in plants exhibit tissue-specific expression, have a considerable number of isoforms, alternative backsplicing (canonical and noncanonical) and alternative circularization patterns (Lu et al, 2015;Sun et al, 2016;Wang et al, 2016;Darbani et al, 2016). The biogenesis of circRNAs is a conserved feature in animal and plant cells.…”
Section: Exosome Regulation Of Lncrnasmentioning
confidence: 99%
“…Intravitreally injected naked siRNA (slightly modified, dTdT) distributed throughout the eye (vitreous, iris, retina, retinal pigment epithelium and sclera) of rabbits when administered at 2 mg/eye, and the pattern of ocular distribution was similar in male and female rabbits ( . Intravitreal injection of miRNAs has been described in the literature using either naked miRNAs in mice , rats (Qin et al, 2016) or using transfection reagent in rats (McArthur et al, 2011) or exosomes in rats (Mead and Tomarev, 2017). Intravitreal injection of miRNAs has been described in the literature using either naked miRNAs in mice , rats (Qin et al, 2016) or using transfection reagent in rats (McArthur et al, 2011) or exosomes in rats (Mead and Tomarev, 2017).…”
Section: Eye Intravitreal Administrationmentioning
confidence: 99%
“…Furthermore, although most circRNAs are considered to be noncoding RNAs, some circRNAs undergo cap-free translation under certain conditions [14]. Recently, increasing numbers of circRNAs have been detected in Arabidopsis thaliana [15][16][17], maize [18][19][20], rice [15,21], tomato [22][23][24], wheat [25][26][27], and grape [28], indicating that circRNAs are widespread in plants. Plant circRNAs are as conserved and tissue specific as animal circRNAs, but their flanking introns do not contain as many repetitive elements and reverse complementary sequences as those in animals [15,16,19,29].…”
Section: Introductionmentioning
confidence: 99%
“…Plant circRNAs are as conserved and tissue specific as animal circRNAs, but their flanking introns do not contain as many repetitive elements and reverse complementary sequences as those in animals [15,16,19,29]. Recent studies have suggested that plant circRNAs play functional roles in developmental processes and stress responses, including the responses to drought, chilling injury, nutrient deficiency, and pathogen invasion [19,20,22,24,25,30]. Based on the functions of animal circRNAs, circRNA-miRNA-mRNA networks have been generated for plants; these networks suggest that plant circRNAs may act as miRNA sponges to regulate functional gene expression [23,25,31].…”
Section: Introductionmentioning
confidence: 99%